Investigating the Effectiveness of Cognitive Vocabulary Strategy Instruction in Raising Learners’ Metacognitive Awareness for Long-Term Mass Lexis Learning - Dib, Naouel (Journal of Human Sciences, 2017)
This paper reports on a study that investigates the role of learning vocabulary and the importance of intentionally instructing learners the techniques of vocabulary learning strategies. This study aimed at implementing a framework of Vocabulary Learning Strategies to enhance learners’ Metacognitive awareness resulting in maximizing their lexis repertoire. It investigates a causal relationship between the direct instruction of VLS and its impact on improving learners Metacognitive strategies towards; learning and retaining vocabulary. It is between the first variable; teaching learners how to learn vocabulary (through the means of Vocabulary Learning Strategies); in other words, the effect of Metacognitive strategy training and the impact of this instruction –the second variable- on raising their Metacognitive awareness to become autonomous and maximize their vocabulary repertoire; leading to the development of lexical knowledge and retention. Our field work consists of a questionnaire designed in accordance and in reliance with Schmidtt’s inventory of Vocabulary Learning Strategies. After gathering preliminary data from questionnaire analysis; a test is designed to serve the aim of spotting the VLS frequency use, and sum of strategies displayed. The test guides the construction of a step by step procedure to teach more elaborate strategies and enable learners become autonomous.